Ensino de porcentagem no 5º ano do Ensino Fundamental: como avaliar? - Almeida, José Reis de (Universidade Federal de São Carlos, 2020)
The proposal of this work was to analyze the difficulties of 5th grade teachers to teach percentage and to propose strategies to evaluate this subject. For this purpose, the guidelines of the Common National Curricular Base for teaching percentage in the 5th grade were consulted, with the objective of knowing the abilities to be reached by the students of this level of education. Then, it was sought to identify the difficulties of teachers in teaching mathematics in 5th grade classes, as well as to elaborate sequences of activities as evaluative strategies, in order to obtain a greater reach in understanding the percentage content. A survey was carried out with 5th grade teachers in the municipal school network of Salto de Pirapora - SP, by means of a questionnaire with semi-structured questions, created to interweave the context of education in a coherent chronology, taking into account a broad panorama regarding training and the teaching profession in Brazil. During the implementation of this study, which began in 2019, some evaluative strategies were thought and executed considering the practice of evaluation as a continuous process, which must be mediated by the teacher and which must assume a diagnostic character for an improvement of the pedagogical practice and, consequently, the learning of the student. However, in 2020, through the current pandemic scenario caused by the new Coronavirus, difficulties were encountered to carry out some of the strategies elaborated and, therefore, adjustments were necessary. Finally, some considerations of the author regarding the importance of the teacher in the elaboration, execution/accompaniment and evaluation of the pedagogical process are presented, which importance was evidenced in the context of remote classes.
Percentage teaching in the 5th year of elementary school: how to evaluate?
Keywords: Profissão docente; Ensino de matemática; Porcentagem; Avaliação da aprendizagem; Teaching profession; Math teaching; Percentage; Learning evaluation; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM